Politics and religion : the basics - Haynes, Jeffrey, 1953- (Basics., 2026)
Politics and Religion: The Basics provides a concise introduction to the complex interactions between politics and religion in both domestic and international contexts.This book examines the role of religion in shaping political systems, behaviours and debates worldwide. By introducing some of the most prominent religions, it explores their impact on contemporary politics and sheds light on key topics such as religious nationalism, gender inequality, religious terrorism and the struggle for religious freedom. Using case studies from countries including Iran, the USA, France, China and Turkey, it highlights pivotal events such as Iran's 1979 revolution and addresses modern controversies such as the rise of religious nationalism. Broader discussions on democratisation, globalisation and secularisation are integrated with theoretical insights and practical examples, offering a comprehensive overview of the field.Aimed at undergraduate students in political science, international relations, and religious studies, this book is also a valuable resource for scholars. With its clear structure and real-world relevance, it provides an ideal starting point for understanding the dynamic relationship between politics and religion.